Comparative analysis of laparoscopic and laparotomic panhysterectomy costs in patients with early stage endometrial cancer - O. A. Smirnova; A. M. Belyaev; I. V. Berlev; A. V. Rudakova; A. P. Karitskiy (ABV-press, 2017)
Endometrial cancer (EC) is the third most common cancer. It comprises almost 10 % of all malignant tumors in women. Peak morbidity is observed at advanced age (62-64 years) and is associated with excess weight. At the time of diagnosis more than 70 % of patients have stage I disease and most of them have a concomitant pathology: diabetes, thrombosis, or hypertension. These patients require a low-trauma panhysterectomy which can be performed laparoscopically or laparotomically. Due to improvement of technological equipment in hospitals and development of surgical and anesthetic techniques, frequency of laparoscopic surgeries at large medical institutions is increasing. Comparative long-term results of oncological treatment allow to pose a problem of comfort in the postoperative period as a reason to prioritize laparoscopicaccess. In order to include the surgery into standard practice, it is beneficial to calculate economic costs for each type of surgical access. Objective. Evaluation of effective costs of panhysterectomy performed laparoscopically and laparotomically for treatment of early stage endometrial cancer. Materials and methods. We performed a retrospective analysis of medical histories of 170 patients with stage I EC who underwent panhysterectomy at the N. N. Petrov Research Institute of Oncology in 2010-2017. Calculations of direct medical costs took into account costs of surgery, drug therapy, treatment of complications, and in-patient care. Indirect costs were based on statistical data on salaries in 2016 and employment in the Russian Federation.Results. For laparoscopic panhysterectomy we observed significant decrease in intraoperative blood loss (82 %), number of drugs, rate of early postoperative complications (mostly associated with postoperative wound healing), and duration of postoperative rehabilitation characterized by short hospital stay and quick return to work. Cost component of the above-mentioned trends amounts to decrease in cost value of 4,000-5,000 rubles for every patient. Conclusions. In long-term perspective, initial investments into high-tech minimally invasive techniques lead to economic benefits due to decrease in costs of in-patient care and treatment of postoperative complications and quick rehabilitation. At the same time, at early stages of EClaparoscopic surgeries don't affect oncological prognosis for these patients.